ANALISA PENERAPAN SUPPLY CHAIN MANAGEMENT BERBASIS SISTEM ERP TERHADAP KINERJA PT NESTLE - William William; Indra Miftahul; Azizul Syukriansyah; Egintal Imanuel Sembiring; Alif Via Indira Rinaldo (LP2M Universitas Bina Bangsa, 2022)
This study aims to determine and analyze the effect of the application of ERP-based suplly chain management on the company's performance of PT Nestle Indonesia. The method used in this research uses library research. Library research using journal articles and books related to this research. This research data collection technique is carried out by collecting data, both journal articles and books. The results showed that the collaboration and ERP implemented by PT. Nestle has a positive impact on the company, especially on the development of the company which until now has remained consistent in producing and distributing products on target. Because articles on the application of ERP and at PT Nestle are still limited, the recommendation for further research is to conduct research in the field to find out more about the influence of application and ERP on Nestle's SCM Performance